Zinc and Iron Enrichment in Wheat Grain Through Soil Amendments: Enrichment of Zinc and Iron in Wheat (Biological Sciences - PJSIR, 2022)
Among staples being consumed globally, wheat (Triticum aestivum L.) ranks at top. However, it is low in bioavailable Zn and Fe engendering nutrition problems in the populace consuming it as major calorie intake source. Biofortifcation, a grain enrichment approach, adjudicated as tenable, economical and smartly executed one. A pot experiment was conducted using different levels of Zn and Fe (2.5, 5.0,7.5 mg/Kg soil) fertilization. Maximum significant grain yield increment over control observed with Zn 7.5g/Kg (60.5%) followed by Zn 5.0 mg/Kg (56%). Grain Zn and Fe contents were at maximum (36.20 and 33.75 µg/g over control i.e., 21.76 and 17.65 µg/g, respectively) with their highest doses i.e. 7.5 mg/Kg soil. Estimated human bioavailability of Zn by trivariate model was enhanced by 67.4 and 46% over control with Zn 7.5 mg/Kg and Zn+Fe 5.0+5.0 mg/Kg, respectively. Estimated Fe bioavailability also increased maximally with Fe 5.0 mg/Kg. The protein content in grain significantly enhanced by the treatments applied in combination of zinc and iron, maximum with Zn+Fe 5.0+2.5 mg/Kg. Conclusively, fertilization approach found feasible in enriching wheat grain with micro minerals Zn and Fe.